A+ Certification for Dummies 2nd Edition - Gilster, Ron (Hungry Minds, 2011)
The Computer Technology Industry Association (CompTIA) A+ certification proves that you're a capable hardware technician, capable of upgrading, troubleshooting, and fixing problems related to physical devices (such as memory chips and video cards) in Intel-compatible personal computers. A+ Certification for Dummies is designed to help you review for the two A+ exams--Core Hardware (220-201) and Operating System Technologies (220-202)--and it succeeds at that goal. It's also worth reading if you're not interested in A+ certification, but want to know enough to change out your own hard drives and install expansion cards without the help of a technician.